FUNDAMENTALS OF MODERN BIOLOGICAL TERMINOLOGIES AND NOMENCLATURES - Khalimova Mohigul Rustamovna (Galaxy International Interdisciplinary Research Journal, 2024)
Understanding the principles of compiling terms of biological nomenclature and being able to use Latin terminology is an important part of the professional training of every biologist. In biology, Latin is still the only international official language. Latin and Greek are the building blocks with which new botanical and zoological terms are created.